The influence of public corruption and female political representation on infant mortality in Asia and the Pacific - Mendoza, Teresa B. (School of Economics, University of the Philippines Diliman, 2018)
This study primarily aims to examine the relationship of political and institutional factors to infant mortality in Asia and the Pacific. This is of high relevance as many countries in the region have seen strong economic growth over the past decades along with higher public health funding, yet infant and child mortality rates remain high, falling short of the Millennium Development Goals (MDG). According to Transparency International (2010) and the United Nations Development Program or UNDP (2016), breakdowns in governance and corruption have been major obstacles to attaining MDGs. The UNDP also noted that attaining progress in women_s empowerment in policy making has proven to be difficult, impeding development goals. Building on these lessons, the ensuing post_2015 Sustainable Development Goals (SDGs) uphold accountable governance and gender equality as among its fundamental elements. Using data covering 28 countries in the Asia Pacific region, this study found that strong oversight at the executive branch of government, and less or no corruption and embezzlement at the executive and legislative branches associate with lower infant mortality. This study also found an equally negative relationship between infant mortality to women political representation, and infant mortality to public goods type of spending as opposed to particularistic or pork spending. Overall, the results suggest that greater attention should be given to governance and institutional factors which are important contributors to improving infant health and survival.